Comprehensive transcriptome analysis of AP2/ERFs in Osmanthus fragrans reveals the role of OfERF017-mediated organic acid metabolism pathway in flower senescence - Zou, Jing-Jing; Zhang, Jun; Wang, Xiaoqian; Xia, Hui; Zeng, Xiangling; Cai, Xuan; Yang, Jie; Zeng, Jin; Li, Zeqing; Zhang, Guifu; Chen, Hongguo (Frontiers in Plant Science, 2024)
Osmanthus fragrans is an ethylene-sensitive flower, and the flower senescence was mediated by Ethylene-Responsive Transcription Factors (OfERFs). A total of 227 OfERFs were identified from O. fragrans, which were classified into five subfamilies: AP2(35), DREB (57), ERF (125), RAV(6) and Soloist (4). Gene composition and structural analysis indicate that members of different subfamilies have different gene structures and conserved domains. Their gene promoter contains various functional responsive elements, including auxin, jasmonic acid and other responsive elements. Among them, 124 OfAP2/ERF genes have expressed at any stage of flowering, and ten of them may play roles in flowering or senescence. By comparative transcriptome analysis, OfAP2/ERFs affected by ethephon (ETH) and 5-Azacytidine (Aza) treatment were divided into three categories, which have various target gene sets. Importantly, these target gene sets participate in similar or different biological processes and metabolic pathways, suggesting that ethylene and DNA hypomethylation have crosstalk and unique mechanism in regulating the flower senescence of O. fragrans. Co-expression analysis revealed several key OfAP2/ERFs played a central role in organic acid metabolism and biosynthesis of branched chain amino acids (BcAAs), among which OfERF017 was selected for further functional analysis. Over-expression of OfERF017 leads to significant enrichment of genes in organic acid metabolism pathways, which leads to a decrease in organic acid levels and promoting the flower senescence of O. fragrans. Together, these results give insights into the characteristics and functional analysis of OfAP2/ERF genes in O. fragrans.